2013
DOI: 10.1007/s00776-013-0455-5
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of lumbar spinal stenosis, using the diagnostic support tool, and correlated factors in Japan: a population-based study

Abstract: BackgroundFew studies have examined the prevalence of lumbar spinal stenosis (LSS) in the general population. The purposes of this study were to estimate the prevalence of LSS and to investigate correlated factors for LSS in Japan.MethodsA questionnaire survey was performed on 4,400 subjects selected from residents aged 40–79 years in Japan by stratified two-stage random sampling in 2010. The question items consisted of lower-limb symptoms suggestive of LSS, the diagnostic support tool for LSS (LSS-DST), demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 24 publications
1
80
0
2
Order By: Relevance
“…Yabuki et al, in an assessment of Japanese individuals between 40 and 79 years old, found a significant association between lumbar spinal stenosis and the incidence of debilitating comorbidities, including urological disorders and osteoarthritis, as well as severe depressive symptoms. 49 The authors reported an adjusted odds ratio of severe depressive symptoms to be as high as 3.39. In an assessment of 100 patients with clinically diagnosed lumbar spinal stenosis, Sinikallio et al found a significantly greater incidence of clinically significant depression (20%) compared with that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Yabuki et al, in an assessment of Japanese individuals between 40 and 79 years old, found a significant association between lumbar spinal stenosis and the incidence of debilitating comorbidities, including urological disorders and osteoarthritis, as well as severe depressive symptoms. 49 The authors reported an adjusted odds ratio of severe depressive symptoms to be as high as 3.39. In an assessment of 100 patients with clinically diagnosed lumbar spinal stenosis, Sinikallio et al found a significantly greater incidence of clinically significant depression (20%) compared with that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the same cohort in their study, they showed that the overall prevalence of symptomatic LSS was 9.3 %, and the prevalence increased with age, particularly in women [40]. Yabuki et al [41] estimated the prevalence of LSS using a diagnostic support tool in their population-based study of 2666 subjects with a mean age of 60 years, and they showed that the prevalence of symptomatic LSS was 5.7 %, increased with age, and was particularly high in subjects aged 70-79 years ([10 %), irrespective of sex. In Europe, a large community-dwelling cohort study from Sweden that included 3009 old men found that 22 % of the participants had sciatic pain [12].…”
Section: Etiologymentioning
confidence: 91%
“…The prevalence of LBP caused by specific pathology of serious nature such as malignancy, spinal fracture, infection, or cauda equine syndrome requiring secondary or tertiary health care has been reported to range between < 1%-4% in the primary health care setting [5,6] . Furthermore, nerve root problems associated with radiculopathy or spinal stenosis are thought to explain approximately 5%-15% of cases [7,8] . Medical imaging studies have highlighted that approximately 50% of younger adults and 90% of older adults have degenerative findings and large variations in lumbar spine morphology [9] .…”
Section: Introductionmentioning
confidence: 99%